MiR-141 Suppresses the Migration and Invasion of HCC Cells by Targeting Tiam1 - Liu, Ying (Public Library of Science, 2014)
BACKGROUND: We have demonstrated that T lymphoma invasion and metastasis 1 (Tiam1) gene is associated with the poor prognosis of patients with hepatocellular carcinoma (HCC), and we used a computational approach to identify miR-141 as a Tiam1-targeting microRNA (miRNA). Here, we explored the function of miR-141 and the relationship between miR-141 and Tiam1 gene in HCC. METHODS: The miR-141 expression in HCC tissues and cell lines was detected and its roles in regulation of HCC cell proliferation, migration and invasion and target gene expression was investigated. Tiam1 was identified as a novel target of miR-141. Ethics statement: our study was approved by the Nanfang Hospital Medical Ethics Committee Ethics statement. Written informed consent was obtained before collection. RESULTS: Based on in situ hybridization (ISH) analysis, miR-141 was down-regulated in the same HCC samples. Kaplan-Meier analysis demonstrated that patients with low miR-141 expression had poorer overall survival rate than that of the patients with high miR-141 expression. Furthermore, multivariate Cox regression analysis indicated that miR-141 could serve as an independent prognostic factor in HCC. MiR-141 significantly inhibited in vitro cell proliferation, migration and invasion as proved by gain- and loss- of function studies, while the mRNA and protein levels of Tiam1 were reduced in cells over-expressing miR-141. Moreover, Tiam1 treatment antagonized this effect, while knockdown of Tiam1 by Tiam1 short hairpin RNA (shTiam1) induced inhibitory effects. CONCLUSIONS: These findings indicated that miR-141 functions as a tumor suppressor and inhibits the migration and invasion of HCC cells by targeting Tiam1, which may provide novel prognostic and treatment strategies for HCC patients.